Prognostic significance of high levels of lipoprotein (a) and C-reactive protein in coronary artery disease - Bansal, Vanita; Bansal, Kunal; Kaur, Sukhraj (International Journal of Research in Medical Sciences, 2025)
Background: Inflammatory markers have been associated with clinical outcome in patients with coronary artery disease (CAD). Atherosclerotic cardiovascular disease is the leading cause of mortality, accounting for more than 15 million deaths worldwide every year. The present study was done to evaluate the role of serum C-reactive protein (CRP) and serum lipoprotein (S. Lp) (a) in CAD. Methods: Sixty patients admitted in Guru Nanak Dev Hospital, Amritsar and sixty healthy subjects were included, and they were followed up for 180 days for any major cardiovascular events after the treatment. Clinical parameters like S. Lp (a) and S. CRP levels were evaluated as risk factors for coronary artery disease and as predictors of major cardiovascular events (such as the occurrence of cardiac death, ischemic stroke or myocardial infarction and mortality. Results: Patients were further categorized into three groups based on serum Lp (a) and serum CRP levels: group A: S. Lp (a) levels >30 mg/dl and S. CRP >5 mg/l, group B: S. Lp (a) levels >30 mg/dl and S. CRP levels were normal, group C: S. Lp (a) levels <30 mg/dl and S. CRP >3 mg/l. Patients with S. Lp (a) >30 mg/dl and S. CRP levels >5 mg/l had a significantly lower survival than the other two groups. When compared with normal healthy subjects S. Lp (a) and S. CRP levels were statistically higher in patients of ACS. Conclusion: The adverse effects of elevated S. Lp (a) levels and S. CRP levels on cardiovascular system have been associated with endothelial dysfunction, inflammatory cells migration and infiltration, oxidative stress, and fibrinolysis inhibition. These inflammatory processes together lead to cardiovascular events and high levels of these inflammatory markers leads to high mortality rates.